School feeding or general food distribution? Quasi-experimental evidence on the educational impacts of emergency food assistance during conflict in Mali - Aurino, Elisabetta; Tranchant, Jean-Pierre; Diallo, Amadou Sekou; Gelli, Aulo (UNICEF Office of Research, 2018)
We rely on a unique pre-crisis baseline and five-year follow-up to investigate the effects of emergency school feeding and general food distribution (GFD) on children’s schooling during conflict in Mali. We estimate programme impact on child enrolment, absenteeism and attainment by combining difference in differences with propensity score matching. School feeding led to increases in enrolment by 11 percentage points and to about an additional half-year of completed schooling. Attendance among boys residing in households receiving GFD, however, declined by about 20 per cent over the comparison group. Disaggregating by conflict intensity showed that receipt of any programme led to rises in enrolment mostly in high-intensity conflict areas and that the negative effects of GFD on attendance were also concentrated in the most affected areas. Conversely, school feeding mostly raised attainment among children residing in areas not in the immediate vicinity of the conflict. Programme receipt triggered adjustments in child labour. Thus, school feeding led to lower participation and time spent in work among girls, while GFD raised children’s labour, particularly among boys. The educational implications of food assistance should be considered in planning humanitarian responses to bridge the gap between emergency assistance and development by promoting children’s education.